A nonstandard finite difference technique for singular Lane-Emden type equations. Issue 5 (25th July 2019) - Chapwanya, Michael; Dozva, Robert; Muchatibaya, Gift
Abstract : Purpose: This paper aims to design new finite difference schemes for the Lane–Emden type equations. In particular, the authors show that the schemes are stable with respect to the properties of the equation. The authors prove the uniqueness of the schemes and provide numerical simulations to support the findings. Design/methodology/approach: The Lane–Emden equation is a well-known highly nonlinear ordinary differential equation in mathematical physics. Exact solutions are known for a few parameter ranges and it is important that any approximation captures the properties of the equation it represent. For this reason, designing schemes requires a careful consideration of these properties. The authors apply the well-known nonstandard finite difference methods. Findings: Several interesting results are provided in this work. The authors list these as follows. Two new schemes are designed. Mathematical proofs are provided to show the existence and uniqueness of the solution of the discrete schemes. The authors show that the proposed method can be extended to singularly perturbed equations. Originality/value: The value of this work can be measured as follows. It is the first time such schemes have been designed for the kind of equations.